PRETRANSITIONAL PHENOMENA IN THE REGION OF STRUCTURAL PHASE TRANSITION IN POTASSIUM SULFATE - Aliev Amil R.; Akhmedov Isa R.; Kakagasanov Murad G.; Aliev Zakir A. (Конденсированные среды и межфазные границы, 2019)
Purpose. The Raman spectroscopy methods were used to study the structural-dynamic properties and molecular relaxation processes in crystalline potassium sulfate K2SO4 in the temperature range from 293 K to 900 K. Results. The temperature dependences of the position of the maximum v (frequency), width w, and intensity I of the spectral band corresponding to fully symmetric vibration were analyzed v1(A) of sulfate ion SO42–, in the spectral range from 963 cm–1 to 976 cm–1. With increasing temperature, the oscillation frequency decreases. At approximately 650 K, certain features of the temperature dependence v(T) take place. With a further increase in temperature, the frequency continues to decrease. At the point of the structural phase transition of the fi rst kind (Ts = 854 K), the decrease in frequency is stopped. With increasing temperature, the width increases, and the intensity decreases. At approximately 650 K, certain features of the temperature dependences w(T) and I(T) take place. The decrease in intensity stops and in the temperature range 650–850 K, the intensity remains almost constant. In the fi rst order structural phase transition (Ts = 854 K), the intensity decreases. The width growth at a temperature T ≈ 650 K is suspended, and then again the width begins to increase. Closer to the fi rst-order structural phase transition (Ts = 854 K), the width growth slows down and at the point of the fi rst-order structural phase transition (Ts = 854 K), the width decreases. Conclusions. It was established that in crystalline potassium sulfate K2SO4 the structural phase transition of the fi rst kind is extended. At the phase transition temperature (Ts = 854 K), the width increases sharply, and the frequency decreases sharply, decreasing with a further increase in temperature. The existence of a pre-transition region in the studied crystalline potassium sulfate K2SO4 was found. This pre-transition region takes place in the temperature range from 650 K to Ts = 854 K.